The readiness of final-year nursing students’ clinical competency and intention to work in clinical setting: a systematic review - Jamaludin, Thandar Soe Sumaiyah; Ilias, Damia; Nurumal, Mohd. Said; Che Hasan, Muhammad Kamil; Win, Kyu Kyu; Ariyanto, Heri (IIUM Press, 2025)
Background: The transition from student to professional nurse requires not only academic preparation but also a high level of clinical competency, practical readiness, and commitment to clinical work. This systematic review examines the clinical competency, readiness for practice, and intention to work in clinical settings among final-year nursing students. Methods: A comprehensive literature search was conducted across Scopus, IIUM Discovery Service, and Google Scholar using Boolean operators, covering the period from 2017 to 2023. Following the PRISMA guidelines, thirty-one relevant articles were selected and critically appraised using validated tools, including the Joanna Briggs Institute (JBI) checklist, Critical Appraisal Skills Programme (CASP), and the Mixed Methods Appraisal Tool (MMAT). Three key themes emerged from this review: Clinical Readiness for Practice, Clinical Competence, and Intention to Work and Future Employment. Results: The findings indicate that while many final-year nursing students possess adequate clinical knowledge and basic technical skills, significant variations exist in their ability to confidently apply these competencies in real-world clinical settings. Factors influencing clinical readiness and competence include the extent of hands-on clinical exposure, the quality of supervision and mentorship, frequency of skill practice, students' self-confidence, and perceived workplace support. Furthermore, students' intention to pursue clinical roles after graduation is closely linked to these experiences and perceptions. Conclusion: This review provides essential insights for nursing educators and policymakers, emphasizing the need to optimize clinical education, enhance the quality of clinical placements, and strengthen support systems to better prepare nursing students for seamless entry into the clinical workforce